Aquatic and wetland plants of Puerto Rico. I. Pteridophyta - Rodulio Caudales; Efrén Vega Hernández; Antonio Sánchez Pérez; Henry Alain Liogier (Anales del Jardín Botánico de Madrid)
A description of the aquatic and wetland families of Pteridophytes in Puerto Rico is presented herein. Included are brief descriptions of each family, genus and species, and, when appropriate, keys for genera and species accompany the descriptions. The distribution of each species is also documented with maps, as well as with information on some ecological characteristics of each species.